Medical student advising during virtual residency recruitment: results of a national survey of internal medicine clerkship and sub-internship directors - Irene Alexandraki; Nadia Ismail; Cindy J Lai; Nicholas S Duca; Temple Ratcliffe; Michael Kisielewski; Amber T. Pincavage (Medical Education Online, 2023)
ABSTRACTIntroduction The residency application process is a critical time for medical students. The COVID-19 pandemic prompted changes to the residency recruitment procedures with the conversion of interviews to a virtual format. For medical school advisors guiding students on an all-virtual residency application process brought uncertainty to their advising practices. Thus, this study aimed to identify advising practices during the 2021 virtual application cycle.Methods We administered an IRB-exempt national survey through the Clerkship Directors in Internal Medicine to 186 internal medicine core/co-/associate/assistant clerkship directors and sub-internship directors representing 140 Liaison Committee on Medical Education-accredited U.S./U.S.-territory-based medical schools in spring 2021. The 23-question survey was designed and pilot-tested by faculty-educators and leaders with expertise in undergraduate medical education. Data analysis included paired t- and z-tests and thematic analysis of open-ended questions.Results The institutional response rate was 67% (93/140) and individual rate 55% (103/186). Half of the respondents felt prepared/very prepared (40% and 13% respectively) for their advising roles. Compared to pre-pandemic cycles, respondents advised a typical student in the middle-third of their class at their institution to apply to more residency programs (mean 24 programs vs 20, p < 0.001) and accept more interviews (mean 14 interviews vs 12, p < 0.001). Sixty-three percent (64/101) of respondents spent more time on student advising; 51% (51/101) reported more students asked them for informal advice. Fifty-nine percent (60/101) of respondents reported their advisees were able to assess a residency program ‘somewhat well;’ 31% (31/101) expressed that residency recruitment should remain entirely virtual in the future.Conclusion The transition to virtual residency recruitment due to COVID-19 prompted advising practices that may have contributed to application inflation and increased advising workload. Future studies should explore longitudinal outcomes of virtual interviews on student success to guide best practices in how to advise students during residency recruitment.